Neuroimaging of pediatric tumors of the sellar region—A review in light of the 2021 WHO classification of tumors of the central nervous system - Maia, Rúben; Miranda, André; Geraldo, Ana Filipa; Sampaio, Luísa; Ramaglia, Antonia; Tortora, Domenico; Severino, Mariasavina; Rossi, Andrea (Frontiers in Pediatrics, 2023)
Sellar/suprasellar tumors comprise about 10% of all pediatric Central Nervous System (CNS) tumors and include a wide variety of entities, with different cellular origins and distinctive histological and radiological findings, demanding customized neuroimaging protocols for appropriate diagnosis and management. The 5th edition of the World Health Organization (WHO) classification of CNS tumors unprecedently incorporated both histologic and molecular alterations into a common diagnostic framework, with a great impact in tumor classification and grading. Indeed, based on the current understanding of the clinical, molecular, and morphological features of CNS neoplasms, there have been additions of new tumor types and modifications of existing ones in the latest WHO tumor classification. In the specific case of sellar/suprasellar tumors, changes include for example separation of adamantinomatous and papillary craniopharyngiomas, now classified as distinct tumor types. Nevertheless, although the current molecular landscape is the fundamental driving force to the new WHO CNS tumor classification, the imaging profile of sellar/suprasellar tumors remains largely unexplored, particularly in the pediatric population. In this review, we aim to provide an essential pathological update to better understand the way sellar/suprasellar tumors are currently classified, with a focus on the pediatric population. Furthermore, we intend to present the neuroimaging features that may assist in the differential diagnosis, surgical planning, adjuvant/neoadjuvant therapy, and follow-up of this group of tumors in children.